Competitiveness of a Specialist: Undergraduates’ Expectations and Strategies - Emelyanova N.A.,; Voronina E.A. (Психолого-педагогические исследования)
The article tackles the problem of competitiveness of university graduates. The study sample is represented by the students of the Faculty of Management. The authors analyze differing views on competitiveness among employers and graduates, and characteristics of key competencies required to obtain and keep a job. A survey among the final-year students was aimed at studying their perceptions of their own competitiveness, job ambitions and expectations. The respondents’ attitudes towards labour market opportunities and career prospects were revealed. The strategies that the future managers use to improve their employability were described. The obtained results may be used to develop and include in the curricula some components of skills which enable the development of a competitive personality.